2012
DOI: 10.1371/journal.pone.0033134
|View full text |Cite
|
Sign up to set email alerts
|

Knock-Down of Core Proteins Regulating MicroRNA Biogenesis Has No Effect on Sensitivity of Lung Cancer Cells to Ionizing Radiation

Abstract: Recent studies underline the important role of microRNAs (miRNA) in the development of lung cancer. The main regulators of miRNA biogenesis are the ribonucleases Drosha, Dicer and Ago2. Here the role of core proteins of miRNA biogenesis machinery in the response of human non-small and small cell lung carcinoma cell lines to treatment with ionizing radiation was assessed. We found that Drosha and Dicer were expressed at higher levels in radioresistant but not in sensitive cell lines. However, down-regulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 26 publications
0
17
0
Order By: Relevance
“…The obvious next question is whether they actively influence how cells deal with radiation injury. Two studies looked at miRNAs’ role on a global level by knocking down key components of the miRNA processing and silencing machinery: DROSHA, DICER, and AGO2 [44,45]. After γ-radiation, endothelial cells have increased rates of apoptosis, and knockdown of either DICER or AGO2 sensitizes them to IR [44].…”
Section: Mirnas That Affect Cellular Radiosensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The obvious next question is whether they actively influence how cells deal with radiation injury. Two studies looked at miRNAs’ role on a global level by knocking down key components of the miRNA processing and silencing machinery: DROSHA, DICER, and AGO2 [44,45]. After γ-radiation, endothelial cells have increased rates of apoptosis, and knockdown of either DICER or AGO2 sensitizes them to IR [44].…”
Section: Mirnas That Affect Cellular Radiosensitivitymentioning
confidence: 99%
“…After γ-radiation, endothelial cells have increased rates of apoptosis, and knockdown of either DICER or AGO2 sensitizes them to IR [44]. However, knockdown of all three proteins individually did not change the number of apoptotic cells in non-small cell lung cancer cell lines [45]. This difference could possibly be due to cell types, the degree of knockdown by siRNAs, or the doses of IR used, for instance, that differ between the two studies [44,45].…”
Section: Mirnas That Affect Cellular Radiosensitivitymentioning
confidence: 99%
“…The distinctive sensitivity of these pathways suggests the autonomous activation of the two response pathways rather than a repaired DNA damage response. Nevertheless, Surova et al, 52 els of microRNA-103/107 are associated with metastasis and poor outcome. Functionally, microRNA-103/107 award migratory capacities in vitro and empower metastatic dissemination of otherwise non aggressive cells in vivo.…”
Section: -13mentioning
confidence: 99%
“…Surova et al [150] found up-regulated the overall expression of miRs in the cells by a higher expression of DROSHA and DICER enzymes. They revealed that these cells were more radioresistant compared to the cells with a lower expression of miRs.…”
Section: Role Of Mir-1 and Mir-21 In The Heart Injury Caused By Radiomentioning
confidence: 99%